Reliability Test of The Timed Up and Go Test in Elderly People with Knee Osteoarthritis - Komalasari, Dwi Rosella; Motik, Annisa Firsita (Universitas Muhammadiyah Surakarta, 2024)
Introduction: Osteoarthritis (OA) of the knee is a degenerative disease in elderly. Pain is a common problem that can decrease balance ability in static and dynamic balance. The Timed Up and Go test (TUG) is one of the tests that could be used to evaluate dynamic balance. However, the reliability of this test in knee OA has not been proven in Indonesia. Therefore, this study aimed to determine the reliability of TUG in elderly with OA knee, especially for test-retest and inter-rater reliability. Methods: This study was an observational study method with a methodological research approach. There were 58 respondents involved in this study who were taken by purposive sampling and met the inclusion and exclusion criteria. Result: Analysis test revealed test-retest reliability and inter-rater reliability have ICC 0.982 and 0.995 (excellent). The test-retest has α=0.991 (excellent), p<0.001, and r=0.962 (very strong correlation). Meanwhile, inter-rater reliability was obtained α=0.997 (excellent), p<0.001, and r=0.990 (very strong correlation). Conclusions: Therefore, the TUG test is reliable for test-retest and inter rater as a measure of dynamic balance as well recommended for elderly with knee osteoarthritis.